ANALYSE DU SUIVI DES ECHANTILLONS DE LA PARALYSIE FLASQUE AIGUE EN REPUBLIQUE DEMOCRATIQUE DU CONGO. Cas de la Division Provinciale de Santé de la Tshopo en 2019. - , Salomon OTOWANGE MANDEFU Y.; Leonard LIFOFA OTAKAWAE,; Elysée Hortence AKUKU-KIANGAINO,; Fabrice OTOLITO TOMILALO,; Jean Claude TUMBA KALIMSI, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
The comprehensive polio eradication initiative will still be relevant only if the surveillance systems for acute flaccid paralysis are regularly evaluated.In an effort to improve the practice of acute flaccid paralysis surveillance service providers in the effort to eradicate polio, a follow-up analysis of samples from acute flaccid paralysis in the Democratic Republic of Congo has was carried out in 2019. This is a descriptive study with a cross-cutting aim. It involved the analysis of 172 cases of acute flaccid paralysis notified in the Provincial Health Division of Tshopo, including 128 cases at the Kisangani branch and 44 cases at the Lokutu branch. Data were collected at the level of the Health Zones which notified the cases of acute flaccid paralysis. The expected results were as follows: the peaks in the distribution of cases notified by epidemiological week were observed during the months of April, June, September and December; 10% of samples from the Kisangani Antenna (n = 128) are taken after 48 hours against those from the Lokutu Antenna (5%); the proportion of samples from the Kisangani branch (54%) and Lokutu (52%) are kept in the provinces beyond 3 days; χ2 = 0.03512, dl = 1 and p-value = 0.8513; the quality of samples is evaluated at 64%, the rate of non-polio AFP (10), the surveillance index is greater than 2.5 both at the level of the Provincial Health Division (n = 6.4) and at the levels of two Antennas (Kisangani and Lokutu): 7.0 and 4.5 respectively.Polio eradication is dependent on improving the quality of acute flaccid paralysis samples encroached on by extended stays (> 3 days or 72 hours) at conservation site levels, poor road infrastructure, lack of means of transport, distance from the National Laboratory, difficult geographic access in DR Congo.